L’armonia della scultura nell’opera di Antonella Zazzera, tessitrice di luce (Materiali di Estetica. Terza serie, 2024)
The author discusses Antonella Zazzera's sculptural work, emphasizing her approach to integrating light and form through woven copper. He explores how Zazzera's sculptures transcend traditional artistic boundaries by blending physical materials with ethereal light, creating a dynamic interplay that invites philosophical reflection on art's spiritual dimensions. The essay highlights the transformative experience of viewing Zazzera's work, which challenges conventional perceptions of sculpture.
Keywords: Antonella Zazzera; philosophy; Sculpture; sculpture light